Ketamine blocks bursting in the lateral habenula to rapidly relieve depression - Yang, Yan; Cui, Yihui; Sang, Kangning; Dong, Yiyan; Ni, Zheyi; Ma, Shuangshuang; Hu, Hailan (Nature (London), 2018)
The N -methyl- d -aspartate receptor (NMDAR) antagonist ketamine has attracted enormous interest in mental health research owing to its rapid antidepressant actions, but its mechanism of action has remained elusive. Here we show that blockade of NMDAR-dependent bursting activity in the ‘anti-reward center’, the lateral habenula (LHb), mediates the rapid antidepressant actions of ketamine in rat and mouse models of depression. LHb neurons show a significant increase in burst activity and theta-band synchronization in depressive-like animals, which is reversed by ketamine. Burst-evoking photostimulation of LHb drives behavioural despair and anhedonia. Pharmacology and modelling experiments reveal that LHb bursting requires both NMDARs and low-voltage-sensitive T-type calcium channels (T-VSCCs). Furthermore, local blockade of NMDAR or T-VSCCs in the LHb is sufficient to induce rapid antidepressant effects. Our results suggest a simple model whereby ketamine quickly elevates mood by blocking NMDAR-dependent bursting activity of LHb neurons to disinhibit downstream monoaminergic reward centres, and provide a framework for developing new rapid-acting antidepressants. The rapid antidepressant activity of ketamine results from reversal of increased burst firing and synchronization in the lateral habenula in rat and mouse models of depression. A burst of activity for antidepressants The lateral habenula (LHb) is a region of the brain that is associated with aversion and other negative emotions. Hailan Hu and colleagues present a pair of papers in this week's issue on the role of burst firing in LHb neurons in depression in rats. First, they show that ketamine, a drug that can be used as an antidepressant, blocks LHb neuron bursting activity, and that both NMDAR and low-voltage-sensitive T-type calcium channels (T-VSCCs) are required for the drug to be effective. In the second study, the authors identify a potential mechanism for regulating this bursting behaviour that could represent a new therapeutic target. Levels of an astroglial potassium channel, Kir4.1, covary with the degree of membrane hyperpolarization and bursting activity of LHb neurons, as well as depression-related behaviours in various rodent models. The team suggest that blocking LHb neuron bursting activity could revive reward centres in the brain and elevate mood, and provide a model framework for developing rapid-acting antidepressants.